Methane fluxes in the foreland soil of Longxiazailongba Glacier on the Tibetan Plateau - Xing, Tingting (PANGAEA, 2022)
Glacier foreland soil was always considered as methane sink. However, there is still a lack of methane dynamics in the foreland soil of mountain glaciers , which are flooded by meltwater in the melting season. In present study, methane fluxes in foreland hollow and hummock soils were measured in June (pre-melting season) and August (melting season) 2020, using polyvinylchloride cylindrical (PVC) tubes . In the pre-melting season, the methane flux was -3.76 ± 9.84 μg·m-2·h-1, and significantly increased to 13.95 ± 12.44 μg·m-2·h-1 in the glacier melting season. Methane flux variations were also observed in the microtopography. Methane flux was -8.29 ± 9.44 μg·m-2·h-1 in hollow soils in the pre-melting season, which was significantly higher than that in hummock soils (0.78 ± 7.97 μg·m-2·h-1). Conversely, methane flux in melting season was 14.27 ± 12.15 μg·m-2·h-1 in hollow soils, which was no longer significantly different form that in hummock soils (13.64 ± 12.71 μg·m-2·h-1).
Keywords: foreland soil; Methane flux; Tibetan Plateau